Tinjauan Fikih Muamalah Terhadap Penerapan Khiyar Dalam Transaksi E-Commerce - Jamilah Jamilah; Firmansyah Firmansyah (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2018)
The e-commerce transaction is a buying and selling instrument that uses electronic equipment primarily. Online buying and selling as well as traditional buying and selling ethics and norms that must be applied in order to create satisfaction and willingness that is by giving the right khiyar. This study uses library research method which uses theories about khiyar in e-commerce transactions through book literature, journals, related to khiyar in e-commerce transactions.The results of this study can be concluded that the practice of khiyar in e-commerce transactions has been implemented through the policy of the return of goods but not all khiyar can be applied in e-commerce transactions there are only three khiyar that can be applied that khiyar syarat , khiyar aib and khiyar ru'yah.